Status of library automation of college libraries in Mendiola - Ingles, Shirley A. (1996)
The purpose of this study is to present the status of library automation of college libraries in Mendiola. Specifically it aims: 1) to find out the types of library automation employed, 2) to determine the accessibility of the information to the users through the types of automation employed, 3) to determine the kind of services being offered, and 4) to determine the plans for further improvement and implementation toward automation.